Alticola (Aschizomys) macrotis - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Alticola (Aschizomys) macrotis (Radde 1862) [Thomasomys] macrotis Radde 1862, Reise in den Suden von Ost-Sibierien, Vol. 1: 196. Type Locality: Russia, S Siberia, S Krasnoyarsk Krai, Vostochnyy Sayan Mtns. Vernacular Names: Large-eared Mountain Vole. Synonyms: Alticola (Aschizomys) altaica Vinogadov 1933; Alticola (Aschizomys) fetisovi Galkina and Epifantseva 1988; Alticola (Aschizomys) vinogradovi Rasorenova 1933. Distribution: Altai of extreme NW Xinjiang and S Siberia, eastward through Tuvinskaya (Tuva region) and Sayan Mtns, to highlands in Lake Baikal region. Conservation: IUCN – Lower Risk (lc). Discussion: Subgenus Aschizomys . Closely related to the northern A. lemminus (see above), and either not allocated to subgenus (Ellerman, 1941), placed it in the subgenus Alticola (Ognev, 1964), or considered under the subgenus Aschizomys (Gromov and Erbajeva, 1995; Gromov and Polyakov, 1977; Pavlinov and Rossolimo, 1987). Galkina and Epifantseva (1988) described fetisovi as species, but others have included it in A. macrotis or considered its status unclear (Vasil’eva, 1999); Pavlinov et al. (1995 a ) and Pavlinov and Rossolimo (1998) persuasively treated fetisovi as a synonym. Chromosomal variation reported by Bolshakov et al. (1985). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 960, DOI: 10.5281/zenodo.7316535